Personality trait imprints across generations: small fam (REGE Revista de Gestão, 2024)
Purpose: The purpose of this study is to investigate how the congruence between predecessor and successor personality traits (PTs) and the values of their small family business (SFB) contributes to a successful succession transition across generations.Design/methodology/approach: The conceptual model method, which describes an entity and identifies issues that should be considered in a study, was employed in this investigation. It involves a form of theorization that seeks to create a nomological network around the focal concept, to examine and detail the causal linkages and mechanisms at play (Delbridge & Fiss, 2013).Findings: Drawing on the trait activation theory (TAT), this study conceptualizes that the congruence of the successor's PTs with those of the predecessor, as well as the values, traditions, and nature of the assigned task, activate the successor’s PTs and motivate him/her to work diligently for a successful succession transition while preserving the business’ core values established by the founder.Research limitations/implications: This study is an eye-opener for strategists and SFB predecessors to ponder the successor’s PTs disparities across generations. Additionally, it urges them to consider the congruence of SFB’s values and nature of operations with the successor’s PTs for successful succession transition. Thus, such awareness may contribute to stabilizing SFB’s survival rate.Originality/value:The study contributes to the existing literature by answering how predecessor’s and successor’s PTs congruence and SFB’s values and nature of operations congruence with those PTs may contribute to successful succession transition across generations. It also contributes to TAT by thematically explaining the organizational cues to bridge a relationship between entrepreneurial personality traits (EPT) and succession success of SFBs.